Open Geospatial Data, Software and Standards
Open Geospatial Data, Software and Standards provides an advanced forum for the science and technology of Open Data, Crowdsourced Geographic Information, Sensor Web and Open Science for Earth Remote Sensing through the publication of reviews, regular research articles as well as software articles. The journal publishes articles that address issues related, but not limited to, the analysis and processing of open geo-data, standardization and interoperability of open geo-data and services, as well as applications based on open geo-data. The journal is also meant to be a space for theories, methods and applications related to crowdsourcing, volunteered geographic information, as well as Sensor Web and related topics. Last but not the least, the journal aims to publish articles that reflect open science tools and methods applied to remote sensing. The relevance of an international journal on Open Geo-Data and Geosensor Web is supported by the fact that open geo-data is not only related to more democracy and transparency in governance, but it is also a means to promote various economic and social opportunities. Today, open geo-data initiatives are part of a majority of countries' policies on improving access to information. In parallel, crowdsourcing is emerging as a new way to gather and disseminate information directly from the field, in a more flexible manner than through traditional data production methods. Meanwhile, Sensor Web creates a new opportunity for members of the public to access information about their environment without relying exclusively on government agencies. All these channels are changing the way people and organizations interact with their environment and contribute to public life. Open Geospatial Data, Software and Standards offers a unique venue where articles related to this topic can be published to provide a comprehensive view.